Effect of support treatment on electrical properties of heterojunctions n-TiO2/p-Si - Мостовий, Андрій Ігорович; Мар’янчук, Павло Дмитрович; Брус, Віктор Васильович (Eastern-European Journal of Enterprise Technologies, 2012)
Recently, metal oxides with semiconducting properties, such as titanium dioxide (ТіО2), have been widely used in various devices, especially in the photoelectric technology for various purposes. At the same time, the interest to the semiconductor heterojunctions is steadily growing due to their advantages in comparison with homojunctions. Nowadays the heterojunctions are widely used in electronics, lasers and photogalvanization. The article studies the electrical properties of the anisotype heterojunctions n-ТiО2/p-Si obtained by applying thin-film TiO2 on the etched and polished polycrystalline Si supports. Since the electrical characteristics of the components of the heterojunctions and metallurgical boundary affect significantly the performance of the semiconductor devices based on the heterojunctions, such studies are important for the further development of the devices based on the heterojunctions n-ТiО2/p-Si for electronics and solar energy. The dependence of the height of the potential barrier and the subsequent resistance on the method of processing of the silicon supports was studied. It was determined that the tunneling is a dominant mechanism of current transport through the heterostructures under different conditions of the Si surface processing